Homeless Media dan Partisipasi Sosial dalam Praktik Citizen Journalism - Puspitoningrum, Anggun (Expose: Jurnal Ilmu Komunikasi, 2024)
The phenomenon of homeless media is emerging, media practices that build their networks only through social media such as Facebook, Instagram and TikTok. According to Jawa Pos, in Indonesia, identifying homeless media is relatively easy because generally the accounts created will begin with the use of city names (txtdari) such as @aslisemarang, @sejarahwonosobo, @solokini and others. Homeless media is named because it is considered homeless so that it can be present and disappear suddenly. Moreover, homeless media becomes digital media that favorite in Indonesia. Because of the social media user, specifically Instagram according to We Are Social data is the second highest user in is Indonesia. In addition, in Indonesia, Instagram has 90.14 million users as of July 2024 while TikTok ranks fourth with 73.5 million users. This research uses descriptive qualitative methods by applying Rich Media Theory and the concept of social participation. Using primary data sources on three homeless media, namely @aslisemarang @sejarahwonosobo and @solokini with data collection techniques, namely observation and interviews. While secondary data sources are obtained through documentation. The results showed that homeless media practices are easily carried out by citizens without having to have a publishing license and as a press company. In addition, the latest information is packaged with contemporary visuals to attract audiences without having to prioritize journalistic practices.